Carriage of diarrhoeagenic escherichia coli by older children and adults in Accra, Ghana - Opintan, J.A.; Bishar, R.A.; Newman, M.J.; Okeke, I.N. (Transactions of the Royal Society of Tropical Medicine and Hygiene, 2010)
Diarrhoeagenic Escherichia coli (DEC) were sought in stool specimens from 72 adults and children aged over 3 years, who presented with diarrhoea at a hospital in Accra, Ghana, and 72 matched controls. Only diffusely-adherent E. coli were significantly associated with disease in these older individuals (P=0.029). We additionally tested 53 specimens from infants among whom DEC were collectively associated with disease (P=0.012). Enteropathogenic, enterotoxigenic and enteroaggregative E. coli, the most commonly isolated pathotypes from infants with diarrhoea, were frequently recovered from healthy adults. Asymptomatic carriage of DEC by older individuals in Accra may place young children at risk for diarrhoea